Analisis Nilai-Nilai Karakter dalam Al-Qur’an dan Hadis serta Relevansinya terhadap Pendidikan Karakter di Era Modern - Evi Sulfaningsih; Sedya Santosa; Dani Alamsyah (Lembaga Yasin AlSys, 2026)
The moral crisis of the modern era, marked by declining honesty, empathy, and responsibility, as well as pervasive violence and intolerance among young people, underscores the urgency of strengthening character education grounded in Islamic values. This study aimed to identify Islamic character values in the Qur’an and Hadith, the methods for instilling these values, and their relevance to contemporary character education. A qualitative library research method was employed, drawing on Qur’anic verses, hadiths of the Prophet Muhammad, works of Qur’anic exegesis, hadith commentaries, and literature on Islamic education. The data were analyzed using content analysis and thematic descriptive techniques. The findings indicate seven core character values—gratitude, patience, honesty, compassion, justice, responsibility, and sincerity, which encompass both vertical–spiritual and horizontal–social dimensions. In addition, six methods of value internalization were identified, namely role modeling, guidance, motivation, sustained habituation, advice, and organizational structuring, all of which are consistent with modern educational approaches such as role modeling, mentoring, and school culture formation. The study concludes that Qur’anic and Prophetic character values are highly relevant for addressing contemporary moral problems such as dishonesty, low empathy, violence, and intolerance. Its theoretical implications enrich the discourse of Islamic education through the formulation of a comprehensive conceptual framework of Islamic character, while its practical implications include the development of character education policies, the design of a more applicative Islamic Religious Education (PAI) curriculum, value-based instructional strategies, and the strengthening of school–family collaboration in character formation. The study also recommends further empirical research to test the effectiveness of these value internalization methods in real classroom contexts and to develop integrative models of character education.